Geography A geographical themes - Coles, Jo; Parkinson, Alan; Payne, Jo; Ross, Simon (Dynamic learning, 2020)
Equip your students for the OCR GCSE (9-1) Geography A specification with our fully revised second edition Student Book. Our expert author team bring you new and revised case studies and a wealth of practice questions to help your students apply their knowledge to succeed at GCSE. - Maps the content against the specification, providing an easy-to-follow teaching pathway designed by an author team of experienced teachers and examiners - Equips students with the subject knowledge and modern case study examples they need to maximise their potential, with opportunities to undertake developmental activities for each theme - Offers you a whole-class solution for teaching including activities suitable for all learners - Embeds a focus on mathematical and statistical skills throughout by including opportunities to analyse a range of maps, graphs, GIS material and data sources - Prepares students to approach assessment confidently with practice questions of varying difficulty and handy tips for writing successful answers - Highlights possible fieldwork projects and contains guidance on carrying out fieldwork, making it easier to integrate practical and theoretical learning.